Differential Gene Expression in Primary Cultured Sensory and Motor Nerve Fibroblasts - He, Qianru; Shen, Mi; Tong, Fang; Cong, Meng; Zhang, Shibo; Gong, Yanpei; Ding, Fei (Frontiers in Neuroscience, 2019)
Fibroblasts effectively promote Schwann cells migration, proliferation, and neurite regeneration. Whether fibroblasts express different motor and sensory phenotypes that regulate the cell behavior and peripheral nerve function has not been elucidated. The present study utilized whole rat genome microarray analysis and identified a total of 121 differentially expressed genes between the primary cultured motor and sensory fibroblasts. The genes with high expression in sensory fibroblasts were related to proliferation, migration, chemotaxis, motility activation, protein maturation, defense response, immune system, taxis, and regionalization, while those with high expression in motor fibroblasts were related to neuron differentiation, segmentation, and pattern specification. Thus, the significant difference in the expression of some key genes was found to be associated with cell migration and proliferation, which was further validated by quantitative real-time PCR (qPCR). The cell proliferation or migration analysis revealed a higher rate of cell migration and proliferation of sensory fibroblasts than motor fibroblasts. Moreover, the downregulated expression of chemokine (C-X-C motif) ligand 10 (CXCL10) and chemokine (C-X-C motif) ligand 3 (CXCL3) suppressed the proliferation rate of sensory fibroblasts, while enhanced that of the motor fibroblasts. However, the migration rate of both fibroblasts was suppressed by the downregulated expression of CXCL10 or CXCL3. Furthermore, a higher proportion of motor or sensory Schwann cells migrated towards their respective (motor or sensory) fibroblasts, however, few motor or sensory Schwann cells co-cultured with the other type of fibroblasts (sensory or motor, respectively), migrated towards the fibroblasts. The current findings indicated that fibroblasts expressed the distinct motor and sensory phenotypes involved in different patterns of gene expression, biological processes, and effects on Schwann cells. Thus, this study would provide insights into the biological differences between motor and sensory fibroblasts, including the role in peripheral nerve regeneration.